Development of modernity in Singapore : the three “worlds” 1920s-1940s - Lim, Amanda Shi Yee (Nanyang Technological University, 2020)
Many academic articles covered the importance of Singapore’s political history in the development of modernity during the colonial years. Yet, few scholarly articles consider public spaces and entertainment, as significant contributing factors in the trajectory of modernity. Academic sources do not cover much about efforts to develop modernity in Singapore during the pre-war years before the Japanese Occupation. This thesis analyses the significance of amusement parks, specifically, the “worlds” of Singapore, New World, Great World, Happy World, as public spaces that contributed to the development of modernity in Singapore during the pre-war years before the Japanese Occupation. The three “worlds” were public spaces that assembled people from different classes and ethnic groups hence enabling interactions and cultural exchange. This thesis contends that the three “worlds” were crucial public spaces that facilitated to the development of modernity in Singapore by being inclusive and affordable, creating hybrid east-west experiences and exposing the masses to science, technology and unique experiences associated with them.